Perceptions of fisheries compensation schemes by fishing communities in Bangladesh - Smallhorn-West, Patrick; Rahman, Shaila; Khan, A K M Firoz (WorldFish, 2023)
The overall objective of this study was to understand the extent to which fishing communities are aware of, understand the reasons for, and can cope with various fishing ban periods in Bangladesh. In addition, we sought to provide a third-party qualitative assessment of government and NGO supported compensation programs on fishing communities, enabling communities to voice their support and concerns about the impacts they perceived of these programs.